The Effort Of Pamong Praja Police Force In Organizing Street Vendors Toward The Beauty And The Orderly Of Mojokerto City (Study in Pamong Praja Police Force's Office of Mojokerto City) - Ramadhan, Andi Satria (Jurnal Administrasi Publik, 2016)
Abstract: The Effort of Pamong Praja Police Force in Organizing Street Vendors toward The Beauty and The Orderly of Mojokerto City (Study in Pamong Praja Police Force's Office of Mojokerto City). Writers lift the problem about the efforts of Pamong Praja Police Force in Management and Supervision of Street Vendors. Background about that title because increasing the presence of the informal sector like street vendors is feared to add to the problem in urban areas, because its existence is considered to be creating chaos, traffic congestion, and interfere with the cleanliness and the physical attraction of the city. There are need for modification or revision of regulation No. 5 of 2005 which regulates the organizationand development of street vendors in Mojokerto to be adapted to the conditions of the vendors at this time. So as to create a shared understanding between the meaning of the arrangement of vendors set out in the local regulation No. 5 of 2005 on the structuring and development of street vendors in Mojokerto City. writers lift the problem about the effort of Pamong Praja Police Force in Management and Supervision of Street Vendors. Background about that title because increasing the presence of the informal sector like street vendors is feared to add to the problem in urban areas, because its existence is considered to be creating chaos, traffic congestion, and interfere with the cleanliness and the physical attraction of the city. There is a need for modification or revision of regulation No. 5 of 2005 which regulates the organization and development of street vendors in Mojokerto to be adapted to the conditions of the vendors at this time. So as to create a shared understanding between the meaning of the arrangement of vendors that can support the implementation of the restructuring program vendors set out in the local regulation No. 5 of 2005 on the structuring and development of street vendors in Mojokerto City. Â  Â  Keywords: Pamong Praja Police Force, Street Vendors, Organizing Abstrak: Upaya Satuan Polisi Pamong Praja dalam Menata Pedgang Kaki Lima menuju Keindahan dan Ketertiban Kota Mojokerto (Studi di Kantor Satuan Polisi Pamong Praja Kota Mojokerto). penulis mengangkat permasalahan mengenai Upaya Satuan Polisi Pamong Praja dalam Menata dan Mentertibkan Pedagang Kaki Lima. Pilhan tema tersebut dilatar belakangi oleh meningkatnya permasalahan dalam Sector Informal seperti Pedagang Kaki Lima yang dikhawatirkan akan menambah masalah di perkotaan, karena keberadaannya dianggap menciptakan kesemrawutan, kemacetan lalu lintas, dan mengganggu kebersihan dan keindahan fisik Kota. Perlu adanya perombakan atau revisi dari adanya perda no 5 tahun 2005 yang mengatur tentang penataan dan pembinaan pedagang kaki lima di Kota Mojokerto xii untuk disesuaikan dengan kondisi para pedagang kaki lima saat ini.serta perlu adanya ketegasan sanksi yang diberikan dalam penataan dan pembinaan pedagang kaki lima sehingga tidak ada membeda bedakan pedagang satu dengan pedagang lain dan juga perlu adanya sosialisasi tentang penataan dan pembinaan pedagang kaki lima kepada pedagang kaki lima. Perlu adanya komunikasi secara langsung terbuka antara pihak pemerintah Kota Mojokerto dan pedagang kaki lima agar mengetahui kelebihan dan kekurangan masing masing pihak.Sehingga dapat menciptakan persamaan persepsi antara arti dari penataan dan pembinaan pedagang kaki lima sehingga dapat mendukung pelaksanaan program penataan dan pembinaan pedagang kaki lima yang tertuang dalam peraturan daerah no 5 tahun 2005 tentang penataan dan pembinaan pedagang kaki lima di Kota Mojokerto. Kata kunci: Satuan Polici Pamong Praja, Pedagang Kaki Lima, Pengorganisasian